Factors Associated with Neonatal Hyperbilirubinemia in Case Files of All Admitted Inborn and Outborn Neonates in Northwest Ethiopia in 2019 - Meseret Teshome Bogale; Worknesh Akanaw Bogale; Destaye Guadie Kassie; Abebe Woldesellassie; Animut Tamiru (Mashhad University of Medical Sciences, 2021)
Background: Jaundice is a yellow discoloration of the skin and eyes caused by hyperbilirubinemia. Jaundice usually becomes visible on the sclera at a level of 2 to 3 mg/dL. Each year, about 1.1 million neonates develop hyperbilirubinemia in the world the vast majority of whom live in sub-Saharan Africa and South Asia. In 2016, neonatal jaundice was estimated to account for about 8 under-5 mortalities per 100,000 live births worldwide. This study aimed to assess the prevalence and associated factors of hyperbilirubinemia among all the inborn and outborn neonates at University of Gondar Comprehensive Specialized Hospital in Gondar, Ethiopia. Methods: The current institutional-based retrospective cross-sectional study was conducted on 399 case files of all the admitted inborn and outborn neonates at University of Gondar Comprehensive Specialized Hospital within March 2017 to March 2019. The extracted data were entered into Epi Info software (version 7.0) and exported and analyzed using SPSS software (version 21.0). Variables with a p-value of less than 0.2 in the bivariate analysis were included in the final model, and the statistical significance was declared at less than 0.05. Both the size and statistically associated factors affecting the results of neonatal hyperbilirubinemia were the main outcome measures in this study. Results: Overall, 31.6% (n=126) of the admitted neonates developed hyperbilirubinemia. Maternal and neonatal Rhesus (RH) incompatibility, ABO incompatibility, low birth weight, hypoglycemia, and birth trauma were the main statistically significant factors associated with neonatal hyperbilirubinemia. Conclusion: The prevalence of neonatal hyperbilirubinemia in this study was high in comparison to that reported for other studies carried out on neonatal hyperbilirubinemia in some parts of Ethiopia. The major factors causing hyperbilirubinemia in neonates were RH incompatibility, low birth weight, birth trauma, and hypoglycemia. Therefore, by the early prevention and prompt treatment of hyperbilirubinemia in neonates, it is important to prevent or reduce both short-term and long-term complications related to this condition.